PEMBUATAN TEMPE BERBAHAN DASAR BIJI SAGA (Adenanthera pavonina Linn) SEBAGAIRANCANGAN BOOKLETPADA MATERI BIOTEKNOLOGI KONVENSIONALSMA - Halawa, Astika Sari; Mahadi, Imam; Zulfarina, Zulfarina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Saga seeds have the potential to be used as a basis for making tempe. Information and knowledge about conventional biotechnology in making tempewith saga seed raw materials to students can be conveyed through learning resources in the form of booklets. This study aims to produce a design booklet for conventional biotechnology materials for grade XII high schools. The study was conducted at the Biology Education Laboratory of the Teaching and Education Faculty of the University of Riau, the Laboratory of the Faculty of Fisheries and Marine Sciences of the University of Riau in June 2019 to August 2019. This study used the ADDIE model, namely the Analyze and Design stages. The results obtained by the booklet design of conventional biotechnology material class XII high school and provide information on the use of saga seeds as a basis for making tempe.KeyWords:Booklets, Conventional Biotechnology, Saga Seeds, Tempe